2021
DOI: 10.3847/1538-4365/abd020
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of n-resolved State-selective Charge Exchange in Ne(8,9)+ Collision with He and H2

Abstract: Charge exchange between highly charged ions and neutral atoms and molecules has been considered as one of important mechanisms controlling soft X-ray emissions in many astrophysical objects and environments. Whereas for modelling charge exchange soft X-ray emission these data of n and l-resolved state selective capture cross sections are often obtained by empirical and semi-classical theory calculations. With a newly-built cold target recoil ion momentum spectroscopy (COLTRIMS) apparatus, we perform a series o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 88 publications
3
16
0
Order By: Relevance
“…With the registered position and TOF information, the recoil ion momentum along the beam direction, defined as the longitudinal momentum of recoil ions P zr , can be reconstructed. Considering the momentum and energy conservation, the state selectivity of CX can be reflected by the following dynamical relationship (Cassimi et al 1996;Dörner et al 2000;Ullrich et al 2003;Xu et al 2021):…”
Section: Experiments Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…With the registered position and TOF information, the recoil ion momentum along the beam direction, defined as the longitudinal momentum of recoil ions P zr , can be reconstructed. Considering the momentum and energy conservation, the state selectivity of CX can be reflected by the following dynamical relationship (Cassimi et al 1996;Dörner et al 2000;Ullrich et al 2003;Xu et al 2021):…”
Section: Experiments Setupmentioning
confidence: 99%
“…For instance, Beiersdorfer et al (2000) have measured the hardness ratios of the X-ray emissions following CX between 10 bare and hydrogenic ions up to U 91+ and neutrals, and found that the assumptions of the statistical distribution break down at low collision energies. Another significant method is the cold target recoil ion momentum spectroscopy (COLTRIMS) detecting technique (Dörner et al 2000;Ullrich et al 2003), which has advanced the measurement of CX to the point where n- (Ali et al 2010;Xu et al 2021) and l-state selectivity can be resolved (Fisher et al 2002;Zhang et al 2017). However, few measurements are reported particularly for l-resolved capture.…”
Section: Introductionmentioning
confidence: 99%
“…By using COLTRIMS, Abdallah et al (1998) found that measured state-selective capture cross sections of 3d to 7l agree with coupled-channel calculations for 1 keV u −1 , 6.25 keV u −1 , and 25 keV u −1 Ar 8+ CX with He. Xu et al (2021) measured n-resolved capture cross sections for 1 ke V/u-25 keV/u Ne (8,9)+ CX with He and H 2 , and found a good agreement between MCLZ calculations and the measured results for He. Another significant development is highresolution X-ray spectroscopy.…”
Section: Introductionmentioning
confidence: 63%
“…A recent comparison using the data from the EBIT measurements [33] showed that the model and the laboratory spectra differ significantly in both line energies and strengths, for the L-shell charge exchange between nickel ions and neutral particles. Another recent example is that the COLTRIMS measurement by Xu et al [34] showed that the model calculations might differ from the measurements by 20-50% for the state-selective cross sections of Ne 8+ and Ne 9+ charge exchange. In this work, we compile a sample of existing laboratory measurements on charge exchange total cross sections, and state-selective cross sections, as well as characteristic X-ray line ratios, and put forward a systematic assessment of the model accuracy.…”
Section: Introductionmentioning
confidence: 99%